Synthesis of tetraline derivatives through depolymerization of polyethers with aromatic compounds using a heterogeneous titanium-exchanged montmorillonite catalyst. Issue 92 (19th September 2016) - Maeno, Zen; Torii, Hiroyuki; Yamada, Shota; Mitsudome, Takato; Mizugaki, Tomoo; Jitsukawa, Koichiro
Abstract : Synthesis of tetraline derivatives through depolymerization of poly(tetramethylene glycol) with several aromatic compounds is newly developed using a titanium-exchanged montmorillonite catalyst. Abstract : A novel depolymerization of poly(tetramethylene glycol) (PTMG) with benzene to tetralin using titanium-exchanged montmorillonite (Ti 4+ -mont) as a solid acid catalyst is described. This catalyst is applicable to depolymerization of PTMG with some aromatic compounds. This is the first demonstration of the potential use of PTMG as a C4 synthon for organic synthesis.